Increasing Provasculature Complexity in the Arabidopsis Embryo May Increase Total Iron Content in Seeds: A Hypothesis - Roschzttardtz, Hannetz; Bustos, Sofía; Coronas, Maria F.; Ibeas, Miguel A.; Grant-Grant, Susana; Vargas-Pérez, Joaquín (Frontiers in Plant Science, 2017)
Anemia due to iron deficiency is a worldwide issue, affecting mainly children and women. Seed iron is a major source of this micronutrient for feeding however in most crops these levels are too low to meet daily needs. Thus, increasing iron allocation and its storage in seeds can represent an important step to enhance iron provision for humans and animals. Our knowledge on seed iron homeostasis is mainly based on studies performed in the model plant Arabidopsis thaliana, where iron accumulates in endodermis cells surrounding the embryo provasculature. It has been reported that cotyledon provasculature pattern complexity can be modified, thus we hypothesize that changes in the complexity of embryo vein patterns may affect total iron content in Arabidopsis seeds. This approach could be used as basis to develop strategies aimed to biofortify seeds.